(NrUSSKAQ MUZYKALXNAQ LITERATURAs (NWYPUSK (B1s ((NlENINGRADs (NmUZYKAs, 1982)
(Nw SEMXE MIROWYH MUZIKALXNYH KULXTUR RUSSKOJ MUZYKE PRENADLEVIT ODNO IZ SAMYH ZNA^ITELXNYH I PO^ETNYH MEST(B.s
Keywords: (NISTORIQs